Real-Time Neuropsychological Testing for Hydrocephalus: Ultra-Fast Neuropsychological Testing During Infusion and Tap Test in Patients with Idiopathic Normal-Pressure Hydrocephalus - Ilaria Guarracino; Sara Fabbro; Daniele Piccolo; Serena D’Agostini; Miran Skrap; Enrico Belgrado; Marco Vindigni; Francesco Tuniz; Barbara Tomasino (Brain Sciences)
Background/Objectives: Ventriculoperitoneal shunting is a validated procedure for the treatment of idiopathic normal-pressure hydrocephalus. To select shunt-responsive patients, infusion and tap tests can be used. Only gait is evaluated after the procedure to establish a potential improvement. In this study, we present our Hydro-Real-Time Neuropsychological Testing protocol to assess the feasibility of performing an ultra-fast assessment of patients during the infusion and tap test. Methods: We tested 57 patients during the infusion and tap test to obtain real-time feedback on their cognitive status. Data were obtained immediately before the infusion phase (T0), when the pressure plateau was reached (T1), and immediately after cerebrospinal fluid subtraction (T2). Based on cerebrospinal fluid dynamics, 63.15% of the patients presented a resistance to outflow > 12 mmHg/mL/min, while 88% had a positive tap test response. Results: Compared to T0, cerebrospinal fluid removal significantly improved performance on tasks exploring executive functions (counting backward, p < 0.001; verbal fluency, p < 0.001). Patients were significantly faster at counting backward at T2 vs. T1 (p < 0.05) and at T2 vs. T0 (p < 0.001) and were significantly faster at counting forward at T2 vs. T1 (p < 0.005), suggesting an improvement in speed at T2. There was a significantly smaller index at T1 vs. T0 (p = 0.005) and at T2 vs. T0 (p < 0.001), suggesting a more marked improvement in patients’ executive abilities at T2 and a smaller improvement at T1. Regarding verbal fluency, patients were worse at T1 vs. T0 (p < 0.001) and at T2 vs. T0 (p < 0.001). Conclusions: Patients’ performance can be monitored during the infusion and tap test as significant changes in executive functions are observable. In future, this protocol might help improve patients’ selection for surgery.